Implementation of the CITES on Illegal Ivory Trade in Japan - Zamy, Mohammad Wildhan Firmansyah Zam; Nurika, Rizki Rahmadini (The Sunan Ampel Review of Political and Social Sciences, 2024)
Japan is a country that has a domestic market for illegal ivory trade. After the Conference of the Parties (CoP) adopted a resolution regarding the recommendation to close the domestic ivory market, many parties asked Japan to close it. This study aims to describe the implementation of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) regime in dealing with the ivory trade in Japan after the recommendation to close the domestic ivory market that contributes to poaching or illegal trade. This research uses descriptive qualitative research methods and is based on the concept of international regimes initiated by Robert O. Keohane. The results show that CITES' implementation in dealing with the ivory trade in Japan was carried out through two events, namely through the CITES governing body and through cooperation between management authorities and TRAFFIC.